The contribution of vertical explosive strength to sprint performance in children - Hammami, R.; Makhlouf, I.; Chtara, M.; Padulo, J.; Chaouachi, A. (Sport Sciences for Health, 2015)
Purpose: This study aimed to investigate the relationship between the explosive strength ratio, which is the quotient between maximum height achieved after counter-movement jump with arm and maximum height achieved after standing start jump, and the 30-m sprint performance. Method: Eighty-four children performed a series of 30-m sprints, Counter-movement jump with arm (arm-CMJ) and Starting Long Jump (SLJ) (with both legs) in randomized block order during the same testing session. Pearson`s product moment correlation coefficients (r) were used to determine the relationship between the explosive strength ratio and sprint performance. The coefficients of determination (R2) were used to examine the amount of explained variance between tests. Stepwise multiple regression analysis was used to estimate the best predictor model of sprint performance. Results: The correlation coefficient between explosive strength Ratio: arm-CMJ/SLJ, 10, and 30-m sprint time was moderate (r = 0.40 and 0.48 respectively). However, correlation with flying time 10 < 30-m sprint time (r = 0.52) was large. The Ratio: arm-CMJ/SLJ was the best single predictor factor (p < 0.001) of the flying time 10 < 30-m sprint time, and explained 27 % of the variance. Conclusion: For improving sprint performance as well as maximal speed and flying time, coaches could ensure the explosive strength ratio as an index to calibrate sprint development program and also for enhancing sport speed in children. They will be able to use this finding to better test and monitor children`s athletes requiring different skills and to evaluate the effects of speed training in children. ABSTRACT FROM AUTHOR